The dual targeting of EGFR and ErbB2 with the inhibitor Lapatinib corrects high glucose-induced apoptosis and vascular dysfunction by opposing multiple diabetes-induced signaling changes - Benter, Ibrahim F.; Sarkhou, Fatima; Al-Khaldi, Abeer T.; Chandrasekhar, Bindu; Attur, Sreeja; Dhaunsi, Gursev S.; Akhtar, Saghir (Taylor & Francis Ltd, 2015)
The epidermal growth factor receptors, EGFR and EGFR2 (ErbB2), appear important mediators of diabetes-induced vascular dysfunction. We investigated whether targeted dual inhibition of EGFR and ErbB2 with Lapatinib would be effective in treating diabetes-induced vascular dysfunction in a rat model of type 1 diabetes. In streptozotocin-induced diabetes, chronic 4-week oral or acute, ex vivo, administration of Lapatinib prevented the development of vascular dysfunction as indicated by the attenuation of the hyper-reactivity of the diabetic mesenteric vascular bed (MVB) to norephinephrine without correcting hyperglycemia. Chronic in vivo or acute ex vivo Lapatinib treatment also significantly attenuated diabetes-induced increases in phosphorylation of EGFR, ErbB2, ERK1/2, AKT, ROCK2 and IkB-alpha as well as normalized the reduced levels of phosphorylated FOXO3A, and eNOS (Ser1177) in the diabetic MVB. Similar results were observed in vascular smooth muscle cells (VSMCs) cultured in high glucose (25 mM) treated with Lapatinib or small interfering RNA (siRNA) targeting the ErbB2 receptor. Lapatinib also prevented high glucose-induced apoptosis in VSMC. Thus, Lapatinib corrects hyperglycemia-induced apoptosis and vascular dysfunction with concomitant reversal of diabetes or high glucose-induced signaling changes in EGFR/ErbB2 and downstream signaling pathways implying that targeted dual inhibition of EGFR/ErbB2 might be an effective vasculoprotective treatment strategy in diabetic patients.
Keywords: Diabetes; drug repurposing; tyrosine kinase inhibitor; vascular complications; vascular reactivity; vascular smooth muscle cells